Application of a Scientific Approach in Citizenship Education to Understand Human Rights in Elementary School - Nuraisyah, Dara (International Journal of Students Education, 2024)
This study aims to explore the application of a scientific approach in learning Citizenship Education in elementary schools to improve students' understanding of Human Rights (HAM). The scientific approach, which consists of observing, asking, trying, reasoning, and communicating, is believed to be effective in creating an in- depth learning experience and encouraging students to be actively involved in understanding human rights concepts. The research method used is qualitative with data collection through literature studies and analysis of various references. The results of the study indicate that the scientific approach not only improves students' understanding of human rights, but also supports character development such as tolerance, responsibility, and empathy which are very important in shaping their awareness as citizens. This finding is relevant to the implementation of the 2013 Curriculum which prioritizes strengthening students' attitudes, knowledge, and skills.